Professores de arquitetura diante da questão do desenvolvimento humano e da inclusão social das pessoas com deficiência - Mazo, Raquel [UNESP]; Leite, Lúcia Pereira [UNESP] (Universidade Federal do Paraná, 2012)
Professors of Architecture on the Subject of Human Development and Social Inclusion of People With Disabilities Historical-Cultural Psychology believes that the people appropriate the culture and develop themselves by social interactions. The architect acts indirectly on human development by producing spaces that allow varying levels of interaction between individuals. To know if the Brazilian Architecture courses are graduating professionals who facilitate the social inclusion of people with disabilities, this research aimed to investigate the concepts of Architecture teachers of a public university about this theme. After the interviews, the reports obtained were submitted to the categorical-content analysis method. Technical concepts predominated over reflective ones, except for the architecture concept, classified as a knowledge area which brings gains to human life.

A Psicologia Histórico-cultural entende que o indivíduo se apropria da cultura e se desenvolve pelas interações sociais. O arquiteto atua indiretamente sobre o desenvolvimento humano, produzindo espaços que possibilitam variados níveis de interação entre os indivíduos. Para responder se os cursos de graduação brasileiros em Arquitetura formam profissionais que favoreçam a inclusão social das pessoas com deficiência, esta pesquisa investigou a concepção de professores de um curso público de Arquitetura sobre temas relacionados à problemática. Os relatos obtidos em entrevistas foram submetidos à análise de conteúdo categorial. Nos resultados, com exceção da concepção de Arquitetura, entendida como área do conhecimento que traz ganhos à vida humana, predominaram concepções pouco reflexivas e mais técnicas.
Keywords: Psychology; Accessibility; Disability; Teaching; Architecture; Psicologia; Acessibilidade; Deficiência; Ensino; Arquitetura